Role of RNA N6-Methyladenosine Modification in Male Infertility and Genital System Tumors - Liu, Shuai; Lao, Yongfeng; Wang, Yanan; Li, Rongxin; Fang, Xuefeng; Wang, Yunchang; Gao, Xiaolong; Dong, Zhilong (Frontiers in Cell and Developmental Biology, 2021)
Epigenetic alterations, particularly RNA methylation, play a crucial role in many types of diseases development and progression. Among them, N6-methyladenosine (m6A) is the most common epigenetic RNA modification, and its important roles are not only related to the occurrence, progression, and aggressiveness of tumors but also affects the progression of many non-tumor diseases. The biological effects of RNA m6A modification are dynamically and reversibly regulated by methyltransferases (writers), demethylases (erasers), and m6A binding proteins (readers). This review is the first time to focus on the mechanisms of messenger RNA (mRNA) m6A modification in spermatogenesis and male genital system tumors, in particular, its role and potential clinical applications. This review is the first time to focus on the mechanisms of RNA m6A modification in spermatogenesis and male genital system tumors, in particular, their roles and the potential application of RNA m6A in clinical.